2021
DOI: 10.21203/rs.3.rs-134789/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methylene Blue has a potent antiviral activity against SARS-CoV-2 and H1N1 influenza virus in the absence of UV-activation in vitro

Abstract: Methylene blue is an FDA (food and drug administration) and EMA (european medicines agency) approved drug with an excellent safety profile. It displays broad-spectrum virucidal activity in the presence of UV light and has been shown to be effective in inactivating various viruses in blood products prior to transfusions. In addition, its use has been validated for methemoglobinemia and malaria treatment. In this study, we first evaluated the virucidal activity of methylene blue against Influenza Virus H1N1 upon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…Finally, an image-based multicycle replication assay based repurposing screening of a chemical library of 5440 compounds that are approved, in clinical trial, or in preclinical development by Murer, Greber and coworkers at the University of Zurich (Zurich, Switzerland) identified MeBlu as one of two promising candidates (the other being mycophenolic acid) that have low micromolar activity against SARS-CoV-2 (1.4 μM). While Cagno et al reported a good therapeutic index for MeBlu in Vero E6 cell-based assay (TI = 46.1/0.11 = 420) [36], this study by Murer et al with Huh7 cells found it to be even lower (TI = 8.7/1.4 = 6.2) [41] than that obtained here with HEK293T cells (TI = 12–16).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Finally, an image-based multicycle replication assay based repurposing screening of a chemical library of 5440 compounds that are approved, in clinical trial, or in preclinical development by Murer, Greber and coworkers at the University of Zurich (Zurich, Switzerland) identified MeBlu as one of two promising candidates (the other being mycophenolic acid) that have low micromolar activity against SARS-CoV-2 (1.4 μM). While Cagno et al reported a good therapeutic index for MeBlu in Vero E6 cell-based assay (TI = 46.1/0.11 = 420) [36], this study by Murer et al with Huh7 cells found it to be even lower (TI = 8.7/1.4 = 6.2) [41] than that obtained here with HEK293T cells (TI = 12–16).…”
Section: Discussioncontrasting
confidence: 72%
“…For example, Cagno, Tapparel, and coworkers at the University of Geneva (Geneva, Switzerland) found that MeBlu showed preventive or therapeutic virucidal activity against SARS-CoV-2 (as well as influenza virus H1N1) at low micromolar concentrations and in the absence of UV-activation [36]. Their results also suggested that the antiviral activity of MeBlu might result from multiple mechanisms of action as the extent of genomic RNA degradation was higher in presence of light and after long exposure.…”
Section: Discussionmentioning
confidence: 99%